2009
DOI: 10.1007/s12229-009-9028-x
|View full text |Cite
|
Sign up to set email alerts
|

Asymmetric Co-evolution in the Lichen Symbiosis Caused by a Limited Capacity for Adaptation in the Photobiont

Abstract: It is proposed that lichen photobionts, compared to mycobionts, have very limited capacity to evolve adaptations to lichenization, so that the symbionts in lichens do not co-evolve. This is because lichens have (a) no sequential selection of photobiont cells from one lichen into another needed for Darwinian natural selection and (b) no photobiont sexual reproduction in the thallus. Molecular studies of lichen photobionts indicate no predictable patterns of photobiont lineages that occur in lichens so supportin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
14
0

Year Published

2011
2011
2020
2020

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 28 publications
(15 citation statements)
references
References 48 publications
1
14
0
Order By: Relevance
“…In many other lichen fungi, sexual reproductive mode has been reported (Arnerup et al 2004;Högberg et al 2002;Kroken and Taylor 2001;Werth and Sork 2008). Our finding of photobiont clonality is consistent with the concept that photobionts do not undergo sexual reproduction when in the lichen thallus (Ahmadjian 1993;Friedl and Büdel 1996;Hill 2009); thus far, only one study has reported evidence for sexual photobiont populations (Kroken and Taylor 2000).…”
Section: Discussionsupporting
confidence: 90%
“…In many other lichen fungi, sexual reproductive mode has been reported (Arnerup et al 2004;Högberg et al 2002;Kroken and Taylor 2001;Werth and Sork 2008). Our finding of photobiont clonality is consistent with the concept that photobionts do not undergo sexual reproduction when in the lichen thallus (Ahmadjian 1993;Friedl and Büdel 1996;Hill 2009); thus far, only one study has reported evidence for sexual photobiont populations (Kroken and Taylor 2000).…”
Section: Discussionsupporting
confidence: 90%
“…Hill (2009) recently postulated that ‘the mycobiont may acquire [photobiont] strains (species, varieties, forms or genotypes) that are more suitable than others but this is unlikely to have any evolutionary consequences.’ The ability to associate with ecotypically differentiated and locally adapted photobionts would clearly be an evolutionary advantage for a mycobiont and may explain the wide ecological amplitudes of many lichen species.…”
Section: Discussionmentioning
confidence: 99%
“…The genetic structure of a lichen population will be strongly influenced by the manner in which photobionts are dispersed and transmitted to the fungus (Hill 2009). Vertical (or co‐dependent) transmission occurs when the photobiont disperses as part of the vegetative propagule of the lichen, thus presumably representing the predominant process in exclusively or nearly exclusively asexual lichen species (Werth & Sork 2010).…”
Section: Introductionmentioning
confidence: 99%